Kidney disease among adults on tenofovir-based second-line antiretroviral therapy in Dar es Salaam, Tanzania - Sabina F. Mugusi; Grace A. Shayo; Philip G. Sasi; Lulu S. Fundikira; Eric A. Aris; Christopher R. Sudfeld; Ferdinand M. Mugusi (Southern African Journal of HIV Medicine)
Background: Kidney disease is a growing non-AIDS-related comorbidity among people living with HIV (PLWH). Tenofovir disoproxil fumarate (TDF) can result in proximal tubulopathy and acute tubular injury, whereas atazanavir/ritonavir (ATV/r) can cause interstitial nephritis and renal stones, both of which can lead to chronic kidney disease.